2020
DOI: 10.1002/ppul.24799
|View full text |Cite
|
Sign up to set email alerts
|

Maldevelopment of intrapulmonary bronchial cartilage in congenital diaphragmatic hernia

Abstract: Background Pulmonary hypoplasia is an important cause of morbidity and mortality in infants with congenital diaphragmatic hernia (CDH). This study aimed to verify our hypothesis that the abnormal development of bronchial cartilage as well as alveolar immaturity, might play a central role in hypoplasia of the lung in human CDH. Method We retrospectively analyzed autopsied lungs from 10 CDH cases and compared with nine age‐matched controls to assess the bronchial cartilage and alveolar maturity using morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Tando et al 44 Esophageal atresia (EA), a congenital foregut anomaly, affects about 1 in 3000 live births and is associated with significant respiratory morbidity. 46 Donoso et al 47 reported on 47 patients with a history of EA who performed lung function testing at either 8 or 15 years of age in a single-center follow-up study.…”
Section: Congenital Airway and Lung Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tando et al 44 Esophageal atresia (EA), a congenital foregut anomaly, affects about 1 in 3000 live births and is associated with significant respiratory morbidity. 46 Donoso et al 47 reported on 47 patients with a history of EA who performed lung function testing at either 8 or 15 years of age in a single-center follow-up study.…”
Section: Congenital Airway and Lung Anomaliesmentioning
confidence: 99%
“…Two papers sought to clarify aspects of CDH pathogenesis. Tando et al 44 examined autopsied lungs from ten children with CDH, compared to nine age‐matched controls. They observed several abnormalities of bronchial cartilage in the CDH lungs, suggesting that abnormal development of bronchial cartilage may play a role in pulmonary hypoplasia associated with CDH.…”
Section: Congenital Airway and Lung Anomaliesmentioning
confidence: 99%